The Association between TLR4 Gene Polymorphism (TLR4-Rs11536889 G/C) and Urinary Tract Infections Caused by Multidrug-Resistant Bacteria among Iraqi Patients - Radhi, Akram; SEÇİL AKILLI ŞİMŞEK‎ (University of Thi-Qar Journal of Science, 2025)
This current study investigated the association between functional gene polymorphisms Toll-like receptors 4 (TLR4 rs11536889) and susceptibility to multidrug-resistant (MDR) bacterial urinary tract infections (UTIs). A total of 350 urine samples were collected from male and female patients aged 10 to 75 years at Al-Rifae General Hospital in Thi-Qar province, southern Iraq, between July 2022 and January 2023 .All bacterial isolates were identified biochemically and by the VITEK-2 system. All isolates were then confirmed with the 16S rRNA gene and resistance genes were detected using bacterial colonies in a PCR test. Tetra-ARMS-PCR was used to detect TLR4 gene polymorphism (rs11536889). Of these, 150 samples (42.9%) showed positive bacterial growth, while 200 samples (57.1%) were culture-negative. The samples that were positive for bacterial growth were 150 samples, including 30 XDR samples, 20 sensitive to antibiotics, and 100 MDR samples Pathogens isolated from MDR samples included Escherichia coli (44%), Staphylococcus aureus (33%), Klebsiella pneumoniae (10%), and Proteus mirabilis (13%). Genotypic analysis of the TLR4 rs11536889 single nucleotide polymorphism SNP (TLR4 rs11536889) indicated that individuals carrying the homozygous CC and heterozygous GC genotypes exhibited a significantly increased risk of developing MDR UTIs, suggesting a potential role for this SNP (TLR4 rs11536889) in host susceptibility to infection, therefore, this polymorphism may serve as a valuable genetic biomarker for the early diagnosis of UTI susceptibility and could contribute to personalized therapeutic approaches, helping to identify individuals at greater risk for resistant infections and to guide appropriate preventive or treatment strategies.